2022
DOI: 10.21203/rs.3.rs-2055033/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Training old dogs to do new tricks: A general multi-pronged activation approach for natural product discovery in Actinomycetes

Abstract: Natural products are a family of diverse compounds with multiple impactful applications, especially in therapeutics. Recent advances in genomics and bioinformatics have also hinted at vast untapped chemical potential within Nature. However, despite the many strategies available for activation and upregulation of natural product biosyntheses in native and heterologous microbial strains, there is yet to be a generalizable and e cient approach for interrogating diverse native strain collections. Here, we describe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…They also demonstrated that this can be tuned by expression of fatty acyl-CoA synthase (FAS). In this work and prior observations [17], we also observed FAS to be significantly efficient in improving production of silent or low-yielding products. Additionally, similar to observations made previously with notonesomycin production in Streptomyces sp.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…They also demonstrated that this can be tuned by expression of fatty acyl-CoA synthase (FAS). In this work and prior observations [17], we also observed FAS to be significantly efficient in improving production of silent or low-yielding products. Additionally, similar to observations made previously with notonesomycin production in Streptomyces sp.…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, similar to observations made previously with notonesomycin production in Streptomyces sp. A793 and other prior work [7,14,17], we expect that further improvement of yields can be made in regulation of nutrient sources or pleiotropic regulators.…”
Section: Discussionmentioning
confidence: 90%
“…Cultures were then collected, freeze dried and extracted with methanol. The extracts were analysed as described in a previous study (48).…”
Section: Methodsmentioning
confidence: 99%
“…Cultures were then collected, freeze dried and extracted with methanol. The extracts were analysed as described in a previous study [49]. to Qubit ratio of 1.0 to 1.5 were used for Nanopore sequencing.…”
Section: Strainsmentioning
confidence: 99%